Evaluating The Use of Artificial Intelligence for Issuing Fatwas in Islamic Inheritance Cases: A Juristic Study with A Comparison To Gpt-3.5 - Abdulrahman, Manswab Mahsen; Walusimbi, Abdul Hafiz Musa (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2024)
Abstract: The objective of this research is to explore the potential of Artificial Intelligence, specifically GPT-3, in the process of issuing fatwas within the context of Islamic inheritance law. The study assesses GPT-3’s capability to issue fatwas that are consistent with Islamic legal principles, as well as its potential to offer faster response times compared to traditional methods. Additionally, the research investigates whether GPT-3 can make fatwas more accessible to a broader, global audience. It also evaluates the compliance GPT-3.5 with Islamic legal standards, considering the economic impact on social welfare development. The study employs qualitative methods, gathering data from various sources such as books, journal articles, reports, conference papers, and jurisprudence academies. It provides a comprehensive analysis of fatwa significance, the historical development of fatwa issuance, traditional methodologies, and the role of technology in Islamic contexts, including AI and natural language processing. Existing research on the intersection of technology, Islamic jurisprudence, and fatwa issuance is reviewed, with a specific focus on GPT-3’s applications in Islamic inheritance. The paper also outlines the research methodology, presenting the rationale for adopting a mixed-methods approach. It details the data collection process, which focuses on inheritance cases involving issues such as homicide, religious differences, Qur’anic heirs, residuary heirs, distant kindred, exclusion, al-Minbariyyah, al-Radd, al-Umariyyah, al-Akdariyyah, missing persons, and multiple deaths. The findings indicate that GPT-3 provides faster response times compared to conventional methods. However, GPT-3.5 demonstrates inconsistencies, particularly in issuing fatwas related to inheritance distribution in cases involving homicide, religious differences, Qur’anic heirs, residuary heirs, distant kindred, exclusion, al-Minbariyyah, al-Radd, al-Umariyyah, and al-Akdariyyah.